Parent-child relationship as a moderator in the relationship between economic hardship and adolescents' delinquency in divorced families - Esmaeili, Nooshin Sabour; Yaacob, Siti Nor; Tan, Soon Aun (2012)
This study aimed to determine the moderating effect of parent-child relationship in the relationship between economic hardship and delinquency among adolescents of divorced families. A sample of 800 adolescents (424 girls and 376 boys) aged between 15 and 18 years completed the Parental Bond Scale (Van Wel, 1994), Economic hardship Questionnaire (Lasley, 1984), and Youth Self-Report Questionnaire (YSR; Achenbach, 1991). Hierarchical multiple regression analysis unveiled that parent-child relationship play a vital role as a moderator in the relationship between economic hardship and adolescents’ delinquency. When there is low parent-child relationship, the relationship between economic hardship and delinquency is stronger.